Studi Eksperimental High Volume Fly ash Self-Compacting Concrete (HVFA SCC) dengan Penambahan 5% Silica Fume terhadap Sifat Reologi dan Mekanik - Tiorivaldi, Tiorivaldi; Putra Abriantoro, Adji (Jurnal Manajemen Teknologi & Teknik Sipil, 2024)
The development of concrete technology is an important part of supporting sustainable development. This development not only focuses on easy and efficient working methods, but also encourages the use of environmentally friendly materials such as fly ash and silica fume. This research aims to investigate the effect of varying fly ash content with the addition of silica fume on the mechanical and rheological properties of High Volume Fly ash Self-Compacting Concrete (HVFA SCC). Variations in fly ash content (0%, 50%, 55%, 60%, and 65%) with the addition of 5% silica fume. The parameters evaluated include flowability, compressive strength, and permeability.  Optimal flowability (750 mm) was achieved at 50–55% fly ash, making it suitable for complex structural applications. Compressive strength peaked at 48.7 MPa with 50% fly ash due to a balance of cement hydration and pozzolanic reactions, while higher fly ash content led to slight reductions. Permeability significantly decreased as fly ash content increased, from 84.1 mm at 0% fly ash to 6.08 mm at 65%, indicating enhanced matrix densification and water resistance due to fly ash's filler effect and pozzolanic activity. The study concludes that 50% fly ash offers the optimal balance, achieving a flowability of 720 mm, compressive strength of 48.7 MPa, and permeability of 58.7 mm. This research shows the potential of fly ash and silica fume as complementary materials to improve the performance of SCC, while recommending a balanced mix design between workability, strength and durability, supporting the development of environmentally friendly and sustainable concrete